KUHAP DAN SISTEM PERADILAN PIDANA TERPADU - -, SUPRIYANTA (Wacana Hukum, 2009)
Abstract:KUHAP and integrated criminal justice system need some pre requisite to conduct. Based on the elements, the integrity of criminal justice system needs to be synchronized both the structure, substance and the culture. In Criminal Law (The Formal Law)  as it is stated in UU No 8 1981 about criminal law , it is already put the framework to conduct the integrated criminal justice through the arrangement of functional relation mechanism between investigating officer and general prosecutor, investigating officer and court, general prosecutor and court and court/attorney and correctional institution. Key words: KUHAP,  integrated criminal justice system.